تحديد مجموعات قيم بعض الداليات في فضاءات الدوال الممثلة بالتكامل (Latakia University Journal -Basic Sciences Series, 2018)
يقدم هذا البحث طريقة معينة لتحديد مستقرات بعض الداليات العقدية المختارة  في فضاء كاراتيودوري وهو فضاء التوابع التحليلية في قرص الواحدة الذي يحقق الشرط  وأيضاَ في فضاء الدوال النجمية المرتبط معه.  باستخدام  التمثيل التكاملي للدوال تم تحديد منطقة تحول بعض الداليات في كل من هذين الفضائين  من الشكل .   This paper presents a certain method of determining the range of  variability  of some linear  functional defined by the Caratheodory  Class (i.e.  the class  of analytic functions in the unit disk  with a real positive part f(0)=1) and by the Class of Starlike Functions related to it. Using the integral  representation of functions in these classes, some estimations for the functional of the type  have been obtained.